THE ROLE OF ARTIFICIAL INTELLIGENCE AND DISPUTE RESOLUTION IN INDIAN VILLAGES: TRANSFORMING ADR PRACTICES - Davis Panadan Varghese; Sini John (Journal of Dharma, 2024)
Access to justice is a fundamental right in India, yet many, especially in rural areas, struggle with slow, expensive and inaccessible court systems, leading to case backlogs. The integration of Artificial Intelligence (AI) in Alternative Dispute Resolution (ADR) is transforming dispute resolution, offering faster, cost-effective solutions. AI-powered ADR platforms, supported by government digitalization initiatives, are set to revolutionize access to justice. However, a strong regulatory framework is essential to ensure fairness, transparency and accountability. Addressing concerns like algorithmic bias and data privacy is crucial for ethical implementation. If AI systems adhere to higher standards of transparency and explainability, they can enhance ADR governance. Despite challenges, AI powered ADR holds immense potential to improve rural dispute resolution, making justice more accessible, efficient and equitable.